Domesticating Cancer: An Evolutionary Strategy in the War on Cancer - van Niekerk, Gustav; Nell, Theo; Engelbrecht, Anna-Mart (Frontiers in Oncology, 2017)
Since cancer shares the same molecular machinery as the host, most therapeutic interventions which aim to target cancer would inadvertently also adversely affect the host. Additionally, cancer continuously evolves, streamlining its host-derived genome for a new single-celled existence. In particular, short-term clinical success observed with most antineoplastic therapies directly relate to the fact that cancer is constantly evolving. However, the clonal evolution of cancer occasionally also render cancer cells uniquely susceptible to therapeutic interventions, as is exemplified by the clinical relevance of synthetic lethality. Synthetic lethality describes a situation where the simultaneous loss of function in two genes results in lethality, but where a loss of function in either single gene is tolerated. This observation suggests that the evolution of cancer, usually seen as a major clinical challenge, may also afford a key opportunity in lowering on-target toxicities accosted with chemotherapy. As an example, by subjecting cancer to specific selection regimes, cancer can in effect be placed on evolutionary trajectories leading to the development of ‘targetable’ phenotypes such as synthetic lethal interactions. However, such a selection regime would have to overcome a range of obstacles such as on-target toxicity and the selection of an evolvable trait. Since the majority of cancer evolution manifests as a loss of function, we suggest that the induction of auxotrophic phenotypes (i.e. where an organism lose the ability to synthesize specific organic compounds required for growth and thus become dependent on it from dietary sources) may represent an attractive therapeutic option. As an example, animals can obtain vitamin C either by de novo synthesis or from their diet. However, since the maintenance of synthetic pathways is costly, such pathways are often lost if no longer necessary, resulting in the organism being auxotrophic towards the dietary compound. Similarly, increasing the maintenance cost of a redundant pathway in cancer cells is likely to select for clones that have lost such a redundant pathway. Inhibition of a pathway, while supporting the activity of a compensating pathway may thus induce auxotrophism in cancer cells, but not in genomic stable host cells.